Social Emotions in Children's Human Figure Drawings: Drawing Shame, Pride and Jealousy. Issue 6 (28th April 2015) - Bonoti, Fotini; Misalidi, Plousia
Abstract : The study examines children's ability to convey social – as opposed to basic – emotions in their human figure drawings. One hundred children aged 4‐, 6‐ and 8‐years were asked to draw a person experiencing shame, pride, jealousy, happiness, sadness and fear as well as a baseline figure 'feeling nothing'. Drawings were rated in terms of (i) overall emotional expressiveness and (ii) variety and types (face, body/posture and context) of graphic cues used to convey emotion. The effect of age on overall expressiveness and use of these graphic cues was also investigated. The results showed that drawings depicting social emotions were rated as less expressive and presented fewer graphic cues than those conveying basic emotions. Children's developing ability to depict pride, shame and jealousy was largely driven by an increased use of contextual cues in their human figure drawings. As regards the effect of age, it was found that 6‐ and 8‐years old produced more expressive drawings containing a larger range of graphic cues than the 4‐year olds. Copyright © 2015 John Wiley & Sons, Ltd.